Workplace Harassment and Political Participation among Representatives to the Union Parishads in Bangladesh - Imdadul Haque Talukdar; Karin Österman; Kaj Björkqvist (Journal of Educational, Health and Community Psychology, 2020)
AbstractThe aim of the study was to explore the relationship between victimisation from workplace harassment and political participation among the elected peoples’ representatives to the rural local governance, namely the Union Parishads in Bangladesh. A questionnaire was completed by 821 representatives (412 women, 409 men). The mean age was 42.5 years (SD = 6.5) for women and 44.2 (SD = 6.3) for men. The results showed that women were significantly more victimised from verbal, nonverbal, and rational appearing aggression, social isolation, and indirect social manipulation than men. For women, the most common type of victimisation was rational appearing aggression, followed by social isolation, and verbal aggression. For men, the most common type of victimisation was from verbal aggression, all the other types of victimisation appeared rarely. Representatives with low political participation scored significantly higher than those with high participation on all six types of harassment.Five of the six types predicted active political participation negatively. Women were more victimised from five types of workplace harassment than men. Victimisation from workplace harassment predicted low political participation.Keywords: Workplace harassment, political participation, sex differences, Union Parishads,                    Bangladesh